Perceived Usefulness of Educational Technology in Rural Accounting Education: Perspectives from School Management Teams and Teachers in South Africa - Martha Matashu; Emmanuel Khameli (Universitas Pendidikan Ganesha, 2026)
Educational technology plays an important role in improving learning quality and learner performance, including accounting education in rural schools. This study aimed to explore School Management Teams’ and accounting teachers’ understanding and perceptions of using educational technologies to improve accounting learner performance in a rural area of Limpopo Province, South Africa. A qualitative approach was employed using purposive sampling. Data were collected through structured interviews with 12 participants, consisting of school principals, Heads of Department, and accounting teachers. The data were analyzed thematically to identify patterns in participants’ understanding and perceptions. The findings revealed that SMTs and accounting teachers understood educational technology as the use of digital devices, modern applications, communication platforms, and instructional equipment to support teaching and learning. Educational technology was perceived as useful because it saves time, simplifies the delivery of accounting content, enhances learner knowledge, supports syllabus completion, and provides access to learning materials and previous examination papers. These findings indicate that positive perceptions among SMTs and accounting teachers represent an important human capital resource for promoting educational technology adoption in rural schools. The study recommends strengthening infrastructure, connectivity, teacher training, and school leadership support to optimize technology-supported accounting learning.